FRI0585 Importance and Level of Implementation of The EULAR/EUMUSC.net Standards of Care for RA in The Netherlands: Similarities and Discordance between Patients and Health Care Professionals. (15th July 2016) - Hifinger, M.; van Eijk, Y.; Putrik, P.; Ramiro, S.; Woolf, A.; Smolen, J.; Stoffer, M.; Uhlig, T.; Moe, R.H.; Saritas, M.; van de Laar, M.; Vonkeman, H.; et al.
Abstract : Background: To harmonize care, the core concepts of RA care have been formulated in the 16 EULAR/EUMUSC.net standards of care (SOC). To further empower RA patients and help them to monitor their disease, SOC have been converted into a patient checklist. Yet, the SOC have never been applied to patients and health care professionals (HCP) in a daily practice setting. Objectives: To assess the importance, level of implementation and implementation gap of the 16 EULAR/EUMUSC.net SOC among patients with RA and HCPs in the Netherlands. Methods: Dutch patients with RA from two hospitals, rheumatologists as well as nurses of the Dutch Society of Rheumatology completed a questionnaire on the importance and level of implementation (0–10 numeric rating scale (NRS); 10=highest, best) of each SOC. An implementation gap, identifying the SOC with a higher need for implementation, was calculated for all individual SOC: (maximal implementation (10) – reported implementation) X reported importance. Patients completed a NRS on global disease activity. Comparisons across subgroups were analysed with Mann-Whitney test. Results: Overall, 217 patients and 91 HCPs (52 rheumatologists and 39 nurses) were included. The 3 SOC with the highest importance and implementation scores were similar for patients and HCPs, and showed almost no implementation gap (table ). While for both patients and HCPs the implementation gap for alternative therapies was high, it should be noted that its perceived importance was relatively low (patients: 6.5 (3.2) and HCPs 6.2 (2.2)). The remaining important implementation gaps referred to SOC with a low implementation, but a high importance, for both patients and HCPs (table ). Within patients, perceived level of implementation of most of the SOC was lower in those with higher disease activity. No important differences were found between subgroups according to gender, age, disease duration, education or health literacy. Conclusions: In the Netherlands, patients and HCPs share similar opinions on the most important aspects of RA care and agree these SOC are appropriately implemented. However, HCPs identified a need for improvement with regard to early diagnosis and providing a treatment plan to the patient. Patients experienced an unmet need in personalized exercise and access to trustful information. This audit of care using SOC identified areas for improvement for care that should be addressed. Disclosure of Interest: None declared